Marmota (Marmota) broweri Hall and Gilmore 1934 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Marmota (Marmota) broweri Hall and Gilmore 1934 Marmota (Marmota) broweri Hall and Gilmore 1934, Canadian Field Nat., 48: 57. Type Locality: USA, "Point Lay, Arctic Coast of Alaska " Restricted by Rausch (1953:117) to head of Kukpowruk River, Alaska. Vernacular Names: Alaska Marmot. Distribution: Brooks Range of N Alaska (USA) from near coast of Chukchi Sea to Alaska-Yukon border; perhaps also N Yukon (Canada). Conservation: IUCN – Lower Risk (lc). Discussion: Subgenus Marmota (Steppan et al., 1999). Regarded as a synonym of caligata (Hall, 1981) but Rausch and Rausch (1965, 1971) and Hoffmann et al. (1979) considered broweri a distinct species. Steppan et al. (1999) found that broweri is more closely related to the Old World caudata than to Nearctic marmots. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Sciuridae, pp. 754-818 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 800, DOI: 10.5281/zenodo.7316535